EDUKASI DAN PEMERIKSAAN GOLONGAN DARAH UNTUK MENUMBUHKAN KESADARAN KESEHATAN PADA SISWA SMAN 1 PANARUKAN SITUBONDO - Elhany, Nurul Avidhah; Fajar, Muhammad Thoifur Ibnu; Dewi, Yuni Kartika; Hudha, Moh Nuril; Ikbal, Mohammad; Kurniawan, Arif (MIMBAR INTEGRITAS : Jurnal Pengabdian, 2026)
Blood type is a crucial aspect of healthcare services, closely linked to patient safety, both in routine medical procedures and emergencies. Besides its clinical importance, blood type data also holds strategic value in hospital blood supply management. The distribution of blood types in a population varies depending on ethnic, geographic, and genetic factors. The purpose of this activity is to raise public awareness of the importance of regular health checks. Based on the results of the blood type testing activity at SMAN 1 Panarukan, it can be concluded that the blood types of SMAN 1 Panarukan students were O (42%), A (26%), B (24%), and AB (8%). The evaluation of the Community Service Program (PKM) implementation showed that all students who participated in the activity recognized the importance of knowing their blood type and understood the blood type testing procedure.